2022
DOI: 10.1002/cl2.1244
|View full text |Cite
|
Sign up to set email alerts
|

What are the effects of different elements of media on radicalization outcomes? A systematic review

Abstract: Background Most national counter‐radicalization strategies identify the media, and particularly the Internet as key sources of risk for radicalization. However, the magnitude of the relationships between different types of media usage and radicalization remains unknown. Additionally, whether Internet‐related risk factors do indeed have greater impacts than other forms of media remain another unknown. Overall, despite extensive research of media effects in criminology, the relationship between media and radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 258 publications
1
8
0
Order By: Relevance
“…Providing some more clarity, Wolfowicz et al (2021) conducted a meta-analysis where they found that unemployment was a putative risk factor for developing radical attitudes. Although the authors found that unemployment had a small impact, another review suggested that it is related to other factors that have a stronger relationship with radicalization, such as social exclusion (Wolfowicz et al, 2022). In addition, employment has also been a common strategy in prevention and deradicalization/disengagement programs (Lobato & García-Coll, 2022; Wolfowicz et al, 2022).…”
Section: Unemployment and Radicalizationmentioning
confidence: 99%
“…Providing some more clarity, Wolfowicz et al (2021) conducted a meta-analysis where they found that unemployment was a putative risk factor for developing radical attitudes. Although the authors found that unemployment had a small impact, another review suggested that it is related to other factors that have a stronger relationship with radicalization, such as social exclusion (Wolfowicz et al, 2022). In addition, employment has also been a common strategy in prevention and deradicalization/disengagement programs (Lobato & García-Coll, 2022; Wolfowicz et al, 2022).…”
Section: Unemployment and Radicalizationmentioning
confidence: 99%
“…Although various meta-analyses focusing on risk factors for radicalization and violent extremism have been released in the last few years (e.g., Wolfowicz et al, 2020Wolfowicz et al, , 2021Wolfowicz et al, , 2022Zych & Nasaescu, 2022), the purpose of the present meta-analysis is to put into test the SQT and its 3N model by systematically retrieving all relevant quantitative (un)published studies, based on primary data, mobilizing the SQT framework and its 3N model. Precisely, it aims to examine the strength of the association between need, narrative, network, and violent extremism.…”
Section: Objectivesmentioning
confidence: 99%
“…In the present research, however, we chose to focus on the latter as the outcome of interest, whereas the former is considered as an independent variable (referring to the narrative component of the 3N model) because the SQT and its 3N model aim to explain violent behavior . Also, we employ the term violent extremism, instead of behavioral outcome of radicalization, because this is the term employed by the proponents of the SQT (Kruglanski et al, 2009, 2022).…”
mentioning
confidence: 99%
“…Having identified a set of 11 empirical studies, using a range of methods and focusing on several extremist ideologies, the review concludes that there is tentative evidence that exposure leads to radicalization, although it is not clear which level of involvement is needed on the user’s side to become more radicalized. Similarly, Wolfowicz et al (2022) reviewed and integrated experimental and observational evidence in a comprehensive meta-analysis. Based on four experimental studies, the authors obtained a small effect for mere exposure to media content, i.e., with passive study participants, on radicalization outcomes (Hedges’ g = 0.08), which was slightly increased in case of high trait aggression ( g = 0.13).…”
Section: Online Radicalization and Terrorismmentioning
confidence: 99%
“…Next, to the question of how much activity or engagement is necessary online to support radicalization, other work has focused on the type of format and content that is most effective. Wolfowicz et al (2022) , in their meta-analysis, attempted to separate online exposure from other forms of media consumption. Pooling outcomes from 49 observational studies, they conclude that TV consumption carries no effect while active and passive online exposure to radical content are related to risk of radicalization ( r = 0.22 for active, and r = 0.24 for passive online consumption).…”
Section: Online Radicalization and Terrorismmentioning
confidence: 99%